The Influence of Using Ai Applications on the Effectiveness of Student Learning at ITEB Bina Adinata - Febrianti B, Nurul; Darmawan, Rifqhy; As'ad, Ahmad; Iryani, Juniarti (Indonesian Journal Publisher, 2025)
This study aims to analyze the influence of using artificial intelligence (AI)-based applications on the learning effectiveness of students at ITEB Bina Adinata, particularly in five key aspects: the types and frequency of AI usage, effectiveness in understanding course material, time and energy efficiency, learning motivation and satisfaction, and the potential for negative AI usage. The research method employed is descriptive quantitative with a case study approach, using total sampling of 40 students from the Information Systems study program. The research instrument was a closed-ended questionnaire with a Likert scale, analyzed statistically through the calculation of means, percentages, and indicator categorization. The findings show that three main indicators fall into the high category AI usage frequency (79.6%), material comprehension effectiveness (79%), and learning efficiency (78.8%) while the other two fall into the moderate category: learning motivation and satisfaction (72.1%) and potential misuse of AI (60.8%). These results indicate that students generally have a positive perception of AI usage in supporting learning, although attention is still needed regarding internal motivation and ethical awareness. The implications of this study highlight the need for academic policies and learning strategies that promote adaptive, responsible, and balanced AI usage maximizing its benefits while fostering students’ academic character development.